Ageing society and the role of social media. Educational needs of aged and the role of social media in their learning - János Szigeti Tóth (Wydawnictwo Naukowe Uniwersytetu Mikołaja Kopernika, 2014)
The adult education need to be more prepared to open the possibilities for ageing citizens to learn more about the social media and train them in a user friendly method enjoy it. This is a challenging agenda for lifelong learning everywhere in Europe. On the pages below the author divides the text on the following sections: data on the usage of social media, focusing on the Facebook (practically it was not possibility to make an overview on all kind of social media tools, as it is a diverse and fast growing field), data on using the Facebook by age groups, the educational need of aged people internationally, educational needs in Hungary (based on a survey), points concerning to make more accessible the social media ageing people.